3D-printed attachable kinetic shading device with alternate actuation: Use of shape-memory alloy (SMA) for climate-adaptive responsive architecture - Yi, Hwang; Kim, Dongyun; Kim, Yuri; Kim, Dongjin; Koh, Je sung; Kim, Mi Jin (Automation in Construction, 2020)
To find a low-cost and flexibly adaptive building design and construction method in the field of sustainable architecture, the authors attempted to propose a user-fabricable 3D-printed kinetic shading device that is selectively actuatable by a switch between a geared DC motor and a thermomechanical shape memory alloy (SMA) actuator. This approach leverages additive manufacturing, SMA, and origami to suggest a lightweight, motorless, and silently operable kinetic building module with compact actuation parts. User-customization is prioritized in its manufacturing, installation, and operation: the device is made by 3D-printed thermoplastic components and is self-supportively installable. User-engaged operation is considered by involving an app-based remote control, along with sensor-integrated automation. The results of responsive building performance simulation and mockup tests demonstrate that the thermo-responsive building module enables control of solar radiation and light, reducing room temperature dynamically. The study findings speak to the limitations and potential of material-based actuation for adaptive building technologies.
Keywords: 3-D printing; Building performance simulations; Building technologies; Integrated automation; Shape memory alloy actuators; Shape memory alloys(SMA); SMA actuators; Sustainable architecture; 3D printing; Kinetic building; Responsive architecture; Shape memory alloys; SMA actuator